The Effect of Green Accounting and Leverage on Company Financial Performance with Good Corporate Governance as a Moderating Variable - Danur Dara Adelia; Sistya Rachmawati (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2026)
Abstract Purpose – This study aims to obtain empirical evidence on the influence of green accounting and leverage on financial performance with good corporate governance as a moderating variable Design/methodology/approach – This study uses a quantitative research design. The sample consists of 52 property and real estate companies listed on the Indonesia Stock Exchange from 2020 to 2024. The analysis techniques used to test the hypotheses are multiple regression analysis and moderation interaction regression using EViews 9 software Findings – The results of this study indicate that green accounting has a negative effect and is not statistically significant on financial performance. Furthermore, leverage has a negative effect and is not statistically significant on financial performance, and good corporate governance has a negative effect and is not statistically significant on financial performance. However, good corporate governance does not strengthen the influence of green accounting on financial performance, and good corporate governance does not strengthen the influence of leverage on financial performance Research limitations/implications – This study discusses financial performance and other factors such as green accounting, leverage, and good corporate governance, focusing on companies in the property and real estate sector. This study contributes new insights by positioning good corporate governance as a moderating variable that strengthens the relationship to explain variations in corporate financial performance amid increasing demands for sustainable business practices